Dampak Konvensi the United Nation General Assembly Special Session on Drugs 2016 Terhadap Stabilitas Keamanan Negara Mexico - Ariyanto, Khidam Sariyyan; Hanura, Marten (Journal of International Relations, 2020)
In 2016 Mexico tried hard to encourage the United Nations to be able to provide a solution to the problems in their country, namely the cartel war which until now the tension is still felt by the people to create chaos. UNODC as a facilitator and as part of protection against narcotics and terror crimes agreed to hold an annual meeting of UNGASS, which during the meeting as a whole in April 2016 discussed changes in policy on certain compounds to be able to overcome cartel problems that disrupt national security in the country. The UNGASS results were welcomed by countries that really needed a solution rather than a deadlock in solving the problem of war between the cartels, in which the elected President of Mexico in 2016 President Jose Pena Nieto ratified the international policy and hoped for a change in Mexico's security stability. Increasing prediction of narcotics in the category of "hard drugs" which is a form of ineffectiveness as a result of the previous narcotics convention (convention 1961), changes in the legal status of cannabis approved by international organizations is a form of effort to handle cases of narcotics distribution in the world without using violence. The use of the concept of the International Regime according to Stephen D. Kranser which focuses on the creation of norms of a regime and is explained using the Participant Understanding approach in responding to Mexico's participation in creating and implementing the 2016 UNGASS recommendation policy into its national law which is a form of the country's seriousness in overcoming and overcoming resolve cartel problems that interfere with Mexico's security stability.